The Orthopaedic Management of Human Disorganization Syndrome. (June 2020) - Smit, Kevin; So, Judy; Schaeffer, Emily; Armstrong, Linlea; Verchere, Cindy; Mulpuri, Kishore
Abstract : Introduction: Human disorganization syndrome (HDS) is an extremely rare congenital syndrome characterized by a seemingly random distribution of multiple developmental anomalies involving all three germinal layers. Case Report: We report a rare case of a female child whose congenital anomalies are consistent with HDS. The orthopaedic features of this patient include a popliteus pterygium with an associated flexion contracture secondary to an elongated biceps femoris tendon that attached to the gastrocnemius-soleus muscle complex, two finger-like appendages, a tethered cord, a lipomeningomyelocele at the level of L5, and a leglength discrepancy. The patient was treated with a splinting program, release of the biceps femoris tendon at its erroneous insertion from the gastrocs-soleus, and surgical excision of the finger-like appendages. She underwent three subsequent soft-tissue releases to address recurrence of the knee flexion contracture and an anteromedial and lateral distal femoral eight plate procedure for guided growth and slow correction of the remaining flexion deformity. Conclusion: The treatment of HDS can be quite complex and can present with a variety of anomalies with distinctive orthopaedic features correctable with surgical management, including soft-tissue releases, excision of appendages, and growth modulation.